Studies on Gullies: an evaluation of Brazilian scientific production (2009/2019) - Pereira, Juliana Sousa; Rodrigues, Silvio Carlos (Sociedade & Natureza, 2022)
Bibliometrics makes it possible to observe the state of science through academic records. It consists of a fundamental investigation of the production of analytical studies in a determined area of knowledge. This study aimed to provide a profile of the panorama of scientific production in soil erosion by gullies based on the abstracts of theses and dissertations published by researchers in Brazil, in order to identify the institutional actors and contribute to the construction of a solid database able to provide support for future investigations. A total of 127 studies published in the period from 2009 to 2019 were analyzed using the Banco de Teses da Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (Theses Database of the Coordination for the Improvement of Higher Education Personnel) (CAPES). Iramuteq software was used as a textual analysis tool, this being an important resource in the bibliometric study. The results show that the greatest number of thesis and dissertation defenses occurred from 2016 to 2018. There was a predominance of the local scale observed over other scales in all surveys. Geographic science graduate programs are responsible for the largest academic production, corresponding to 47.2% of all publications in the adopted time frame. The Southeast region has the largest number of universities and, consequently, the largest number of tutors of studies focused on the abovementioned theme. It is important to emphasize the importance of the role of institutions in the evolution of science, which is underpinned by the multiplicity of works produced.